Generación sobre la base Sig del mapa geomorfológico, escala 1: 25 000, orientado a la gestión territorial del cantón Balsas, provincia de El Oro. - Jumbo Castillo, Johanna Karina (2018)
Geographic Information Systems are an efficient tool in the characterization, precise location and classification of the geomorphological features, enabling quick integration and representation of multiple attributes. In this perspective, the application of geomorphological cartography is described through the research work entitled "GENERATION ON THE GIS BASIS OF THE GEOMORPHOLOGICAL MAP, SCALE 1: 25,000, ORIENTED TO THE TERRITORIAL MANAGEMENT OF CANTÓN BALSAS, PROVINCE OF EL ORO"; the same one that is sustained to theoretical and methodological level. The mapping of geomorphological units was based on the delimitation of the geoforms according to the fundamentals of the system for the geomorphological mapping of the Ecuadorian Space Institute (IEE), which considers genesis, morphology, morphometry, and constitutive material (lithology) as main factors. The construction of the geomorphological cartography was carried out through the technique of digital photointerpretation, where the geoforms of the study area were identified, delimited and categorized. To determine the quantitative attributes of each relief unit, GIS analysis was used based on the DEM. As a result an interactive and updateable cartographic product was obtained, composed of 64 geoforms, grouped in 8 morphological units.